Consumers' awareness towards aflatoxin contamination in peanut-based products in Klang Valley - Hassan, Nur Adibah; Kamarulzaman, Nitty Hirawaty (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Aflatoxin is one type of toxic that produced by fungi such as Aspergillus flavus and Aspergillus parasiticus (Aycicek et al. 2005). It is the most carcinogenic substances in food and feed especially grain products like maize, wheat, rice, and peanuts. Among agriculture commodities, peanut has been recognized as very vulnerable to aflatoxin contamination. The harmful toxic is very poisonous in the high level of consumption on food and feed. Symptoms of acute aflatoxin include liver damage, liver cancer, and coma depending on gender, age, and health. Aflatoxin is also classified as human carcinogens by the International Agency for Research on Cancer. Consumers’ knowledge about aflatoxin in peanut-based products will increase their awareness on contamination issues. As consumers are more towards healthy conscious and concerned on the food they consume, thus it is important to investigate consumers’ awareness towards aflatoxin contamination in peanut-based products.